1998
DOI: 10.1152/ajpcell.1998.275.3.c740
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Mn SOD in human monocytes without inflammatory cytokine production by a mutant endotoxin

Abstract: Endotoxin selectively induces monocyte Mn superoxide dismutase (SOD) without affecting levels of Cu,Zn SOD, catalase, or glutathione peroxidase. However, little is known about the structure-activity relationship and the mechanism by which endotoxin induces Mn SOD. In this study we demonstrated that a mutant Escherichia coli endotoxin lacking myristoyl fatty acid at the 3′ R-3-hydroxymyristate position of the lipid A moiety retained its full capacity to coagulate Limulus amoebocyte lysate compared with the wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…In addition to charge interactions, we demonstrated the critical role of the interaction between MD-2 hydrophobic residues and lipid A acyl chains. A nonpathogenic penta-acylated LPS lacking the secondary myristoyl chain did not induce immunological responses in human cells (3,30,31). We found that the mutant LPS did not bind to human MD-2.…”
mentioning
confidence: 72%
“…In addition to charge interactions, we demonstrated the critical role of the interaction between MD-2 hydrophobic residues and lipid A acyl chains. A nonpathogenic penta-acylated LPS lacking the secondary myristoyl chain did not induce immunological responses in human cells (3,30,31). We found that the mutant LPS did not bind to human MD-2.…”
mentioning
confidence: 72%
“…However, in contrast to the wild-type LPS, nmLPS fails to induce significant production of TNF␣ and does not induce the phosphorylation and nuclear translocation of MAPK (Tian et al, 1998). These results suggest that induction of TNF␣ and MnSOD in human monocytes by LPS are, at least in part, regulated through different signal transduction pathways.…”
mentioning
confidence: 72%
“…Human mononuclear cells were isolated from venous blood of normal volunteers (after explaining the nature and possible risks of the studies and obtaining informed consents) using Isolymph (Gallard-Schlesinger Industries Inc., Carle Place, NY) as described previously (Tian et al, 1998). Cells (5 ϫ 10 6 /ml in RPMI 1640 plus antibiotics and 10% autologous serum) were allowed to adhere onto tissue culture plates for 2 h. Adherent cells which consisted of approximately 90% monocytes as judged by the nonspecific esterase staining, were used for the current studies.…”
Section: Isolation Of Human Monocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clones from the up-regulated fraction included 68 known genes, 35 expressed sequence tags, and nine novel sequences, whereas clones from the down-regulated fraction included 209 known genes, 111 expressed sequence tags, and five novel sequences. In the up-regulated fraction there were many known PMA-induced genes such as IL-8, tumor necrosis factor ␣, macrophage inflammatory protein 1, and superoxide dismutase 2 (11)(12)(13)(14). There was very little overlap between the up-and down-regulated sets of genes, except for the presence of a small number of microbeads bearing up-regulated B94 (M92357) cDNAs in the down-regulated fraction and some microbeads bearing downregulated 23 kDa basic protein transcript (X56932) in the up-regulated fraction.…”
Section: Analysis Of Differential Gene Expressionmentioning
confidence: 99%